Entrepreneurs Behavior Members of The Indonesian Young Entrepreneur Association: Role of Intention, Attitudes, Contextual Environment, Creativity - Indri Murniawaty; Afifah Nurul Izzah; Nina Farliana (Indonesian Journal of Business and Entrepreneurship, 2022)
Student behavior in entrepreneurship has not been maximized, where some members actually already have a business framework, but it is only a framework and there is no real action. This study aims to analyze the influence of entrepreneurial attitudes, contextual environment, and creativity on entrepreneurial behavior through the entrepreneurial intentions of students who are members of the Indonesian Young Entrepreneurs Association (IYEA) at two universities, namely Universitas Negeri Semarang (UNNES) and Universitas Diponegoro (UNDIP). This type of research is a quantitative study with a student population of members of IYEA UNNES and UNDIP. The sampling technique used was purposive sampling with a sample size of 100 students. The data collection method used an online questionnaire. The method of data analysis is Partial Least Square – Structural Equation Modeling (PLS-SEM) with the Warp-PLS 7.0 program. The results of the study showed entrepreneurial attitudes, contextual environment influences entrepreneurial behavior. Entrepreneurial intentions are proven to be able to mediate the influence between entrepreneurial attitudes and the contextual environment on entrepreneurial behavior. Suggestions in maintaining and improving student entrepreneurship behavior is to be active in participating in various activities, training, and seminars on entrepreneurship.